PERAN BUDAYA KERJA DAN IKLIM KERJA TERHADAP LOYALITAS PEGAWAI BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN LAMONGAN - RAHMAH, AISYATUR (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT   Each agency sets a high job culture and suitable job climate to support the creation of high employee loyalty. Job culture is needed in the activities of organization in achieving goals. Job climate has directly or indirectly by the employees and its can affect employees. Employee loyalty shown by the willingness to work for a longer time. This research aims to describe the job culture conditions and to investigate the role of job culture and job climate on employee loyalty by simultanly and partially in the General Section of Secretariat Lamongan  Regency. This type of research is descriptive research with quantitative research approaches. Sample and population of this research is all staff of internal employees totaling 43 employees. Instrument in this research using a questionnaire. Techniques of data analysis using multiply linear regression. The conclusions of this research are: (1) Conditions of job culture, job climate, and employee loyalty in the the General Section of Secretariat Lamongan Regency is categorized as high. (2) Job culture and job climate contributes to employee loyalty by simultanly and partially in the the General Section of Secretariat Lamongan Regency.      Keywords: Job Culture, Job Climate, Employee Loyalty